Menentukan Portofolio Optimal Dalam Sektor Keuangan Pada Indeks IDX30 Menggunakan Model Markowitz - Shafitri, Rheina; Wulandani, Sabrina Dwi; Salsabila, Keysha Putri; Saniyyah, Safira; Rianto, Muhammad Richo (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2023)
The purpose of this research is to determine the optimal portfolio in IDX30 which is listed on the Indonesia Stock Exchange, and find out returns, expected return variance-covariance, correlation coefficient, expected return, and risk. Based on the results of data analysis for the formation of an optimal portfolio using the Markowitz model on IDX30 shares on the Indonesia Stock Exchange for the period December 2022 to May 2023. The shares that will be analyzed in the optimal portfolio are 5 (shares) as part of the optimal portfolio, namely Bank Central Asia Tbk (BBCA), Bank Rakyat Indonesia Tbk (BBRI), Bank Negara Indonesia Tbk (BBNI), Bank Mandiri Tbk (BMRI), Bank Jago Tbk (ARTO). Before investing in shares, investors should diversify their shares by forming an optimal portfolio, one way is by using the Markowitz model or by using others model.